Research status of biodegradable metals designed for oral and maxillofacial applications: A review - Dandan Xia; Fan Yang; Yufeng Zheng; Yunsong Liu; Yongsheng Zhou (Bioactive Materials, 2021)
The oral and maxillofacial regions have complex anatomical structures and different tissue types, which have vital health and aesthetic functions. Biodegradable metals (BMs) is a promising bioactive materials to treat oral and maxillofacial diseases. This review summarizes the research status and future research directions of BMs for oral and maxillofacial applications. Mg-based BMs and Zn-based BMs for bone fracture fixation systems, and guided bone regeneration (GBR) membranes, are discussed in detail. Zn-based BMs with a moderate degradation rate and superior mechanical properties for GBR membranes show great potential for clinical translation. Fe-based BMs have a relatively low degradation rate and insoluble degradation products, which greatly limit their application and clinical translation. Furthermore, we proposed potential future research directions for BMs in the oral and maxillofacial regions, including 3D printed BM bone scaffolds, surface modification for BMs GBR membranes, and BMs containing hydrogels for cartilage regeneration, soft tissue regeneration, and nerve regeneration. Taken together, the progress made in the development of BMs in oral and maxillofacial regions has laid a foundation for further clinical translation.